PENGARUH COUNTRY OF ORIGIN, GAYA HIDUP DAN PERCEIVED QUALITY TERHADAP KEPUTUSAN PEMBELIAN PRODUK MINISO - Inayah wulandari; Titik Desi Harsoyo (Program Studi Manajemen Fakultas Ekonomi UST, 2023)
This study aims to analyze the effect of Country of Origin, Lifestyle and Perceived Quality on Purchase Decisions for Miniso products. This study used of sample 100 respondents who were at least 17 years old, domiciled in Yogyakarta and had purchased Miniso products for at least the last 6 months. The data collection technique in this study was a survey method, namely a questionnaire. Data on all question items in the instrument test show valid and reliable results. The data in the classical assumption test show results that are normally distributed and this research is free from multicollinearity and there is no heteroscedasticity. The results of this study show: (1) Country of Origin has no significant effect on purchasing decisions for Miniso products. (2) Lifestyle has a positive and significant effect on purchasing decisions for Miniso products. (3) Perceived Quality has a positive and significant effect on Purchase Decisions for Miniso products. Theoretically, this research has implications, namely empirically testing the effect of lifestyle and perceived quality on purchasing decisions for Miniso products. This research also has implications for the Miniso industry to build an image or image for products from the country of origin so influence consumer purchasing decisions.